Huge intermediate-grade myofibroblastic sarcoma in the retroperitoneum revealed by 18F-FDG PET/CT: a case report - Li, Xiaotian; Mei, Tengyue; Wang, Pan; Cai, Jiong; Hu, Xianwen (Frontiers in Medicine, 2024)
Myofibroblastic sarcoma (MS) is a relatively rare malignant bone and soft tissue tumor of myofibroblastic origin, with some characteristics of both smooth muscle cells and fibroblasts.MS can occur at any age and in different areas, especially the head and neck, but is rarely reported retroperitoneally. MS is usually a low-grade malignancy, while the number of moderate and highly malignant reports is rare. Herein, we describe an instance of intermediate-grade myofibroblastoma sarcoma (IGMS) originating from the retroperitoneum, supported by a pathological diagnosis. The 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission computed tomography (PET) /computed tomography (CT) scan revealed a large, borderless mass located retroperitoneally with significantly increased 18 F-FDG uptake, accompanied by adjacent visceral and soft tissue infiltration, and peripheral lymph node metastasis. The patient was treated with chemotherapy for three weeks, but the tumor did not shrink significantly, and the patient gave up treatment and died five months later. Through this case report, the diagnosis and treatment of moderate malignant retroperitoneal myofibroblastoma were discussed, so as to increase clinicians' understanding of the disease.